2010
DOI: 10.1016/j.bone.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Muscle power and physical activity are associated with bone strength in older men: The osteoporotic fractures in men study

Abstract: The purpose of these analyses was to explore whether physical activity score, leg power or grip strength were associated with tibia and radius estimates of bone strength, cortical density, or total bone area. Peripheral quantitative computed tomography (pQCT) was used to compare tibial and radial bone volumetric density (vBMD, mg/cm3), total (ToA, mm2) and cortical (CoA, mm2) bone area, and estimates of bone compressive strength (bone strength index, BSI) and bending strength (polar strength strain index, SSIp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 30 publications
7
52
3
3
Order By: Relevance
“…Our findings are consistent with the Osteoporotic Fractures in Men Study, which has shown that men in the lowest quartile of grip strength had smaller bones, lower cortical area, and stress strain index at the diaphysis of the radius 36. Similarly, in the Hertfordshire Cohort Study, positive associations in men aged 70 years and over between grip strength and diaphyseal periosteal circumference, stress strain index, and cortical bone area were reported 37.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are consistent with the Osteoporotic Fractures in Men Study, which has shown that men in the lowest quartile of grip strength had smaller bones, lower cortical area, and stress strain index at the diaphysis of the radius 36. Similarly, in the Hertfordshire Cohort Study, positive associations in men aged 70 years and over between grip strength and diaphyseal periosteal circumference, stress strain index, and cortical bone area were reported 37.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, grip strength has been demonstrated as a strong predictor of bone strength at the distal radius shaft [24]. Although the 30-s chair stand test has not been used to assess the relationship between lower extremity strength to bone strength, a positive association between peak leg extensor power and estimated bone strength at the shaft and distal sites in the lower leg has been demonstrated in older individuals [29,40]. While this research used seated knee extension equipment versus the sit-to-stand motion, the techniques have been correlated significantly to chair rises in elderly subjects [41], and knee extensor strength and power are associated with improved performance on the 30-s chair stand test [30].…”
Section: Discussionmentioning
confidence: 99%
“…The 30-s chair stand test has been referred to as a functionally relevant measure of lower extremity strength in older adults [26], with the individual performing as many repetitions of a full stand and return to the sitting position in 30 s, without the assistance of the upper extremities [27]. Rapid sit-to-stand performance provided a combined measure of strength and power; both of which have been associated with estimated bone strength in the lower limb [28][29][30]. The 30-s chair stand test is also associated with fall risk and functional ability in older adults [26] and thus clinically is used to assist prediction of future fracture risk.…”
Section: Background Characteristicsmentioning
confidence: 99%
“…(11) Grip strength was positively associated with both aBMD (12)(13)(14)(15)(16) and volumetric BMD (17)(18)(19) at the distal ORIGINAL ARTICLE…”
Section: Introductionmentioning
confidence: 99%